Synergy of photoacoustic and fluorescence flow cytometry of circulating cells with negative and positive contrasts - Nedosekin, Dmitry A. (2012)
[Image: see text] In vivo photoacoustic (PA) and fluorescence flow cytometry were previously applied separately using pulsed and continuous wave lasers respectively, and positive contrast detection mode only. This paper introduces a real-time integration of both techniques with positive and negative contrast modes using only pulsed lasers. Various applications of this new tool are summarized, including detection of liposomes loaded with Alexa-660 dye, red blood cells labeled with Indocyanine Green, B16F10 melanoma cells co-expressing melanin and green fluorescent protein (GFP), C8161-GFP melanoma cells targeted by magnetic nanoparticles, MTLn3 adenocarcinoma cells expressing novel near-infrared iRFP protein, and quantum dot-carbon nanotube conjugates. Negative contrast flow cytometry provided label-free detection of low absorbing or weakly fluorescent cells in blood absorption and autofluorescence background, respectively. The use of pulsed laser for time-resolved discrimination of objects with long fluorescence lifetime (e.g., quantum dots) from shorter autofluorescence background (e.g., blood plasma) is also highlighted in this paper. The supplementary nature of PA and fluorescence detection increased the versatility of the integrated method for simultaneous detection of probes and cells having various absorbing and fluorescent properties, and provided verification of PA data using a more established fluorescence based technique. The principles of integrated photoacoustic and fluorescence flow cytometry using positive contrast for detection of strongly absorbing and fluorescent cells and negative contrast for detection of weakly absorbing and fluorescent cells in blood absorption and autofluorescence background, respectively.